EARLY WARNING SYSTEM: THE ROLE OF WHISTLE-BLOWERS TO REDUCE CORRUPTION IN INDONESIA AND MALAYSIA - Pupung Purnamasari (JRAK, 2023)
This study aims at intending to compile arrangements for early warning against corruption through the activities of informants overseen by the Whistleblowing Protection Act. However, the commitment to eradicate moral decline was the obligation of Indonesian and Malaysian citizens. It is also to distinguish how the Whistle-blowing Protection Act can be used as an initial notification toward acts of corruption. The population used was 260 respondents, of which 130 were from Indonesia and 130 were from Malaysia and used the SEM-AMOS v25 analysis tool. The results of this study indicated that the Whistle-blowing Protection Act is a model of the early notification framework and Pentahelix, especially in preventing fraud and acts of corruption.